Increased QPCT gene expression by the hepatitis B virus promotes HBV replication. - Conghui Zhang; Qingfeng Ma; Wei Wang; Hui Song; Xue Wang; Fengxia Xu; Chengliang Zhu; Xinghui Liu (PLoS ONE)
Glutamine cyclase, an enzyme involved in posttranslational modifications, is encoded by the glutaminyl-peptide cyclotransferase (QPCT) gene. Gene microarray analysis revealed that the QPCT gene was highly expressed in HepG2.2.15 cells compared with that in HepG2 cells. The serum expression level of the QPCT gene was detected by ELISA and was significantly greater in HBV-infected patients than in healthy controls. The mRNA and protein expression levels of the QPCT gene were markedly greater in the HBV-expressing cell lines (HepG2.2.15, and HepG2 and Huh7 cells transfected with the pBlu-HBV plasmid) than in the HepG2 and Huh7 cells. The levels of HBV pgRNA and HBV-DNA copy number, as well as the levels of HBeAg and HBsAg, also increased in the HepG2 and Huh7 cell lines cotransfected with the QPCT gene expression plasmid and the HBV 1.3-fold plasmid. Our study indicated that HBV can promote the expression of the QPCT gene, which in turn promotes the expression and replication of HBV.